Mutation screening for thalassaemia in the Jino ethnic minority population of Yunnan Province, Southwest China. Issue 12 (29th December 2015) - Wang, Shiyun; Zhang, Rong; Xiang, Guangxin; Li, Yang; Hou, Xuhong; Jiang, Fusong; Jiang, Feng; Hu, Cheng; Jia, Weiping
Abstract : Objectives: This study aimed to detect α- and β-thalassaemia mutations in the Jino ethnic minority population of Yunnan Province, Southwest China. Design: A total of 1613 Jino adults were continuously recruited from February 2012 to April 2012. Fasting venous blood samples were obtained to determine haematological variables. Haemoglobin analysis was conducted using high-performance liquid chromatography. Participants with hypochromic microcytic anaemia or positive haemoglobin analysis profiles were confirmed by α- and β-globin genetic testing, including DNA microarray analysis, direct sequencing methods and multiplex gap-PCR assays. Setting: Shanghai Diabetes Institute, Shanghai Key Laboratory of Diabetes Mellitus, Shanghai Jiao Tong University Affiliated Sixth People's Hospital. Results: We found 363 suspected cases by primary screening of haematological variables and haemoglobin analysis. After further genetic testing, four types of α- and β-thalassaemia mutation were detected in 203 out of 363 individuals. Both α 0 - and α + -thalassaemia mutations, -- SEA and -α 3.7, were identified. β-Thalassaemia mutations included CD17 (HBB:c.52A>T) and CD26 (HbE or HBB:c.79G>A). In addition, 13 HbE carriers had coexisting α 0 - or α + -thalassaemia deletions. Clinical haematological variables indicated that, in this study, carriers of all thalassaemic genotypes had more severe hypochromic microcytic anaemia than non-thalassaemic individuals. Conclusions: Our results provide information on the Jino ethnic minority that may be useful for further genetic counselling, prenatal screening and clinical diagnosis of thalassaemia in this region.